Effect of arcelin protein on the biology of Zabrotes subfasciatus (Boheman 1833), in dry beans - Barbosa, Flávia Rabelo; Yokoyama, Massaru; Pereira, Pedro Antônio Arraes; Zimmermann, Francisco José Pfeilsticker (Pesquisa Agropecuaria Brasileira, 1999)
Arcelin is a seed protein found in wild beans (Phaseolus vulgaris) which gives resistance to Mexican bean weevil, Zabrotes subfasciatus (Boheman 1833) (Coleoptera: Bruchidae). Studies were carried out with the objective of estimating the effect of four alleles of protein arcelin (Arc1, Arc2, Arc3 and Arc4) on the biology of Z. subfasciatus. The experiment was carried out in laboratory at Embrapa-Centro Nacional de Pesquisa de Arroz e Feijão, in Santo Antônio de Goiás, GO, Brazil, under non controlled conditions. The highest levels of antibiosis to Z. subfasciatus were observed in Arc1, with reduction in the number of eggs, number of emerged adults, adults longevity. In the line Arc2 only reduction in the number of emerged adults was observed. The lines Arc3 and Arc4 showed low efficiency on the reduction of progeny of Z. subfasciatus and effects in the longevity and egg-adult cycle were not detected. Insect sexual ratio was not altered by the presence of Arc1, Arc2, Arc3 and Arc4 in the seeds.